Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

The synergistic role of non-antibiotic agrochemicals and environmental pollutants in driving antimicrobial resistance in poultry systems - Ambreen Leghari; Faiz Muhammad Khand; Shakeel Ahmed Lakho (Journal of Environmental Chemical Engineering, 2026)

Impact of seasonal temperature shift on leaf senescence physiology and structure of Dalbergia sissoo Roxb. under semiarid conditions - Muhammad Shareef; Waleed Hussain; Fanjiang Zeng; Fatiha Shakeel; Saira Boota; Bo Zhang (Flora, 2026)

Differential eco-photophysiological responses of Halophila stipulacea and H. ovalis across environmental gradients around Rodrigues Island, Western Indian Ocean - Shakeel Yavan Jogee; Marwyn Anasamy; Ashfaaq Muhammad Korimbocus; Kamakshi Maukshada Ramkalam; Sundy Ramah; Vasisht Seetapah; Ranjeet Bhagooli; Deepeeka Kaullysing (Estuarine, Coastal and Shelf Science, 2026)

Retraction Note: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2026)

A hybrid machine learning–Markov chain framework for GCM subset selection and probabilistic regional drought assessment - Muhammad Shakeel; Zulfiqar Ali; Veysi Kartal; Hussnain Abbas; Maysaa Elmahi Abd Elwahab; Rizwan Niaz (Journal of Earth System Science, 2026)

Genomic instability in canine mammary tumors: A comparative focus on loss of heterozygosity and microsatellite alterations with human breast cancer - Faiz Muhammad Khand; Barkat Ali Jatoi; Shakeel Ahmed Lakho; Ambreen Leghari (Mutation Research - Reviews in Mutation Research, 2026)

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Multi-index remote sensing and GIS-based assessment of Shisper Glacier surge dynamics and glacial lake outburst flood hazard in Hunza, Pakistan - Maida Khanum; Yuping Su; Shakeel Mahmood; Kanwal Javid; Jehangir Ijaz; Sheraz Akhtar Gil; Muhammad Irfan Ahamad; Rana Muhammad Zulqarnain (Environmental Monitoring and Assessment, 2026)

Climate change as a driver of bovine mastitis: Impacts on environmental pathogen ecology, host susceptibility, and future mitigation strategies - Ambreen Leghari; Faiz Muhammad Khand; Sheereen Laghari; Shakeel Ahmed Lakho (The Veterinary Journal, 2026)

Next-generation thermal management systems for lithium-ion batteries: Enhancing the performance and safety in electric vehicles - Zahid Bashir; Riaz Hussain; Hafeez Khoharo; Jarrar Ali Jaffri; A.L. Saroj; Shahid Bashir; Jeyraj Selvaraj; Muhammad Shakeel Ahmad (Journal of Environmental Chemical Engineering, 2026)

Dental caries beyond eradication: microbiome centered and equilibrium driven therapeutic strategies - Maryam Jabeen; Huma Hameed; Areej Abdul Razzaq; Muhammad Jamshaid; Muhammad Amish Shakeel; Tehreem Mushtaq (Archives of Microbiology, 2026)

Adsorptive removal of methylene blue from wastewater using sawdust of Cedrus deodara and its composite with iron oxide nanoparticles: a comparative study - Muhammad Shakeel; Shahid Ali; Muhammad Waseem; Bisma Liaqat; Mahnoor Aurangzeb; Aina Noor; Saira Bibi; Uzma Iqbal; Mehmood-ul-Hassan (Environmental Science and Pollution Research, 2026)

Evaluating blue sheep density and conservation needs in Pakistan's high-mountain ecosystems - Shakeel Ahmad; Muhammad Asif; Hussain Ali; Amina Zuberi; Muhammad Ali Nawaz (Journal of Arid Environments, 2026)

A comparative analysis of crop water footprint, practices, and economic water productivity (EWP) in Punjab, Pakistan and Western Australia, Australia - Zohreh Rajabi; Stephen Gray; Shakeel Hayat; Muhammad Atiq Ur Rehman Tariq (Irrigation Science, 2026)
A comprehensive analysis of crop water footprint (WFP), water use efficiency (WUE) and economic water productivity (EWP) between 2010 and 2020 in two climatically and economically diverse agricultural regions: Punjab, Pakistan and Western Australia, Australia was undertaken. Using the Water Footprint Network method and climate, soil and agricultural production data, the study quantified green, blue and grey water footprints for five staple crops in each region. Normalization by local water scarcity and irrigation share was used to compare between the two regions with different water stress levels and irrigation dependence. Results showed that the total crop water requirements in Punjab increased by 12% during the study period due to changing climatic conditions. Cotton and rice had the highest WFP and dependence on irrigation, however generated relatively low economic returns per unit of water, showcasing inefficiency in the current agricultural system. In contrast, rain-fed crops in WA showed lower absolute crop water requirements and lower increases in normalized WFP, with stable WUE and EWP with cereals, showcasing efficient water use under climate-driven limitations. Normalization highlighted the difference in water stress, identifying that Punjab’s irrigation-intensive crops put much greater stress on local water resources than WA crops. Integration of biophysical and economic indicators, when normalizing for water scarcity, provides a strong basis to assess water practice of various agricultural systems. The results indicate the necessity for location-specific approaches: increased irrigation efficiency and suitable crop selection in Punjab; and climate-resilient cropping to maximize water use productivity and economic return in WA.

Recent advances in machine/deep learning frameworks for biochar application in soil amendment and remediation - Muhammad Waqas; Mohsin Nawaz; Rongli Yang; Waseem Tariq; Muhammad Nauman Tahir; Shakeel Ahmad (Applied Soil Ecology, 2026)

Ecology of Shipwrecks Around Mauritius Island: Implications for Optimizing Shipwreck Performance for Marine Biodiversity - Marwyn Anasamy; Brihatee Mattapullut; Homesha Bhurosah; Vasisht Seetapah; Ashfaaq Muhammad Korimbocus; Kamakshi Ramkalam; Ranjeet Bhagooli; Shakeel Yavan Jogee; Deepeeka Kaullysing (Marine Ecology, 2026)
Shipwrecks can function as artificial reefs that enhance marine biodiversity and productivity by providing structurally complex habitats. However, ecological assessments of shipwrecks in the Western Indian Ocean, including Mauritius Island, remain scarce. This study presents the first systematic ecological evaluation of five shipwrecks around Mauritius, focusing on their ecological performance in terms of fish assemblages and benthic composition, and identifying environmental thresholds that favour biodiversity enhancement. Belt transects (2 m × 1.5 m) laid across the full width of each wreck were used to quantify fish assemblages, while benthic cover was assessed using line intercept transects. Environmental parameters including light, depth, temperature, dissolved oxygen, pH, salinity, and nutrient concentrations were recorded at each site. Fish biomass and community composition varied significantly among wrecks, with the highest mean biomass (138.6 ± 13.2 g m −2 ) and density recorded at shallower, well‐illuminated, structurally degraded wrecks. In contrast, coral cover peaked (21.9% ± 3.9%) on structurally intact wrecks under similar light regimes. Linear mixed‐model analysis identified light availability and pH as key drivers of fish biomass, while structural integrity supported coral cover. Principal Coordinates Analysis (PCoA) further indicated that depth, nitrate, and pH were key factors structuring both coral and fish assemblages. Building on these patterns, an exploratory framework termed the Optimal Ecological Performance Thresholds (OEPT) was derived to identify indicative environmental and spatial ranges representing conditions that can maximize coral cover and fish biomass. These thresholds provide a preliminary, science‐based reference for guiding future shipwreck deployments and ecosystem‐based coastal management.

Kilometer-scale simulation of atmospheric in-cloud ground icing over complex terrain in Norwegian Arctic - Pravin Punde; Yngve Birkelund; Muhammad Shakeel Virk; Xingbo Han; Trude Eidhammer (Cold Regions Science and Technology, 2026)

A geospatial graph neural network framework for analyzing climate variability impacts on crop yields in northeast Thailand - Muhammad Waqas; Usa Humphries Wannasingha; Angkool Wangwongchai; Shakeel Ahmad; Porntip Dechpichai; Phyo Thandar Hlaing (Theoretical and Applied Climatology, 2026)

Optimizing GCM ensemble selection and weighted MME development for improved drought projection under global climate models simulations - Muhammad Shakeel; Zulfiqar Ali; Hussnain Abbas; Muhammad Mohsin; Mrim M. Alnfiai; Naim Ahmad; Rizwan Niaz (Natural Hazards, 2026)

A Novel Sequential Weighting and Standardisation Framework for Robust Drought Assessment Using CMIP6 Projections - Hussnain Abbas; Muhammad Shakeel; Muhammad Mohsin; Zulfiqar Ali; Amna Nazeer; Rizwan Niaz; Naim Ahmad (International Journal of Climatology, 2026)
In the era of global warming, drought remains one of the most pressing, insidious and complex climatic phenomena. Although Global Climate Models (GCMs) are indispensable for simulating past and future climate patterns, they continue to face persistent challenges in accurately characterising drought under diverse climate conditions due to inherent model uncertainties. Multi‐model ensembles (MMEs) are widely adopted to reduce these uncertainties; however, conventional MME approaches often overlook three critical aspects: (i) the independent relative contribution of individual GCMs, (ii) the influence of point‐wise value deviations and (iii) the sequential order of predictor inclusion in the analysis. Neglecting these factors can result in biassed weighting, reduced interpretability and overestimation of drought severity in subsequent assessments. This study introduces an integrated two‐stage framework, Integrated Ensemble Based on Sequential Predictor Contribution Analysis for Standardised Climate Indices (IEBSPCASCI), for future drought assessment using GCM projections, combining a novel weighting strategy with an optimised drought index formulation. In Stage 1, we propose the sequential relative impact weighting ensemble (SRIWE), a new GCM ensemble weighting scheme that accounts for point‐wise discrepancies and sequential predictor contributions with addressing multicollinearity among models; in Stage 2, we develop the Standardised Partitioned Impact Severity Drought Index (SPISDI), an optimal‐standardisation‐based index enhancing drought severity quantification under future climate scenarios. The proposed IEBSPCASCI framework is applied to 94 locations in Pakistan using 22 GCM from the Coupled Model Intercomparison Project Phase 6 (CMIP6) for the period 1950–2014. The Stage 1 weighting scheme, SRIWE, outperforms conventional MMEs, achieving the highest median and mean Kling–Gupta Efficiency (KGE) (0.2650, 0.2435) and Nash–Sutcliffe efficiency (NSE) (0.2074, 0.1075), and the lowest median and mean values of Mean Absolute Error (MAE) (12.5572, 18.027), indicating superior predictive skill and smaller errors. In stage 2, SPISDI‐based drought assessments reveal a consistent increase in drought severity and frequency in all SSP scenarios. Under SSP5‐8.5, the intensity of drought peaks markedly towards 2080–2100, signalling substantial climate‐induced risks to water resources and agriculture. Steady‐state probability analysis indicates that normal drought conditions dominate; however, extreme drought (ED) and severe drought (SD) events remain significant, with ED peaking at 2.37% (SSP2–4.5, 48 months) and SD reaching 8.6% (SSP1–2.6, 48 months). These findings underscore the urgent need for adaptive water management policies, climate‐resilient agricultural strategies and proactive drought risk governance to mitigate future socio‐economic impacts.

Redundancy‐Resilient Multi‐Criteria Multi‐Model Ensemble Framework for Drought Assessment Under Climate Change - Hussnain Abbas; Muhammad Shakeel; Zulfiqar Ali; Rizwan Niaz; Naim Ahmad; Ali Atif Yassin Ali (International Journal of Climatology, 2026)
Reliable assessment of drought risks under climate change requires robust evaluation of climate models, redundancy‐resilient ensemble construction, and accurate quantification of extremes. Existing approaches often fail to account for non‐linear dependencies, inter‐model redundancy, and spatial performance, limiting the reliability of drought projections. This study introduces Integrated Information‐theoretic redundancy‐resilient ensemble and drought assessment (IIREDA), a multi‐criteria framework that integrates information‐theoretic dependence measures, redundancy adjustment, spatial performance consistency, and advanced ensemble techniques. Applying IIREDA to 22 CMIP6 global climate models (GCMs) across 29 grid stations in drought‐prone Balochistan (1950–2014; projected SSP1–2.6, SSP2–4.5, SSP5–8.5 for 2015–2100), we identify high‐performing models (e.g., CNRM‐CM6‐1‐HR, MIROC‐ES2L) and highlight underperforming models (e.g., CanESM5‐CanOE). Using the novel HC‐GDM ranking, an optimal subset of 11 GCMs is selected, ensuring robust ensemble construction. Ensemble experiments demonstrate that constrained least squares ensembles (CLSE) outperform equal‐weighted, machine learning and probabilistic methods by reducing bias and effectively managing outliers. For drought characterisation, K‐component Gaussian mixture modelling (K‐CGMM) captures extremes more accurately than traditional univariate distributions. Drought assessment using the proposed IW‐GSPI reveals stable conditions under SSP1–2.6, intensification under SSP2–4.5, and persistent multi‐year severe droughts under SSP5–8.5, further supported by Markov chain analysis. In summation, IIREDA advances methodological rigour in climate risk assessment, providing redundancy‐resilient, probabilistic drought projections to inform mitigation and adaptation strategies.

Retraction Note: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2026)

Molecular characterization and genetic diversity of cotton whitefly Bemisia tabaci infesting cotton crops - Qamar Saeed; Muhammad Sagheer; Ummad ud din Umar; Muhammad Taimoor Shakeel; Mahmoud Moustafa; Mohammed Al-Shahrani; Uthman Algopishi; Muhammad Naeem; Mahmoud Ahmed Amer (International Journal of Tropical Insect Science, 2026)

Integrating noninvasive genetics and SECR to estimate snow leopard population in Pakistan - Shakeel Ahmad; Katherine A. Solari; Ian Durbach; Hussain Ali; Shoaib Hameed; Jaffar Ud Din; Muhammad Asif; Dmitri A. Petrov; Muhammad Ali Nawaz (Biological Conservation, 2026)

Development of co-integrated standardized procedure for the joint monitoring, forecasting and probabilistic characterization of climate extremes under global climate models - Aamina Batool; Mahrukh Yousaf; Muhammad Shakeel; Amina Magdich; Reem Alreshidi; Zulfiqar Ali; Veysi Kartal (Theoretical and Applied Climatology, 2026)

Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Potential efficacy of insecticides and plant growth regulators against Oxycarenus hyalinipennis (Costa) during the fruiting stage of cotton (Gossypium hirsutum L.) - Muhammad Saqib Ajmal; Muhammad Farhan; Sajjad Ali; Qaiser Shakeel; Habib Ali; Ammara Riaz; Javaid Iqbal; Konul Ahmadova; Muhammad Sarmad; Muhammad Sajjad (International Journal of Tropical Insect Science, 2026)

Overcoming global climate model inconsistencies in drought projection with the development of dual divergence correlation weighting scheme over Pakistan - Mahrukh Yousaf; Amara Farooq; Sadia Qamar; Naim Ahmad; Muhammad Shakeel; Aamina Batool; Zulfiqar Ali; Veysi Kartal (Acta Geophysica, 2026)

Effect of a GnRH antagonist on the fate of the dominant ovarian follicle and the emergence of the next follicular wave in alpacas - Jaswant Singh; Miruna Munteanu; Muhammad A. Shakeel; Gregg P. Adams (Theriogenology, 2026)

An expert-driven digital platform for decision support in sustainable building retrofitting - Hafiz Muhammad Athar Farid; Shamaila Iram; Hafiz Muhammad Shakeel; Richard Hill; Vladimir Simic (Energy and Buildings, 2026)

Brucellosis seropositivity and risk factors in small ruminants and livestock workers: A cross-sectional study in Punjab, Pakistan - Muhammad Shakeel Khaliq; Muhammad Hassan Mushtaq; Abdul Rehman; Farhat Nazir Awan; Muhammad Avais; Tariq Jamil (Preventive Veterinary Medicine, 2026)

Computational prediction of thermomechanical properties in ionic liquid-modified MWCNT/carbon fiber composites - Bilal Ghafoor; Faisal Ghafoor; You Jinglin; Muhammad Shakeel Ahmed; Masood Ahmed; Silvia Tamborim; Sandro Campos Amico; Henri Stephan Schrekker (Next Research, 2026)

Assessing debris-covered glaciers using geospatial techniques in the Hindu Kush Region, Pakistan - Shakeel Mahmood; Fatima Salman; Mariam Sarwar; Muhammad Irfan Ahamad (Cold Regions Science and Technology, 2026)

Solubility measurements of R143a, R23 and R116 with [HMIM][TF2N] and [BMIM][BF4] - Nimra Javed; Muhammad Salman; Yiran Wang; Peiji Wang; Asim Shakeel; Xiangyang Liu; Maogang He (International Journal of Refrigeration, 2025)

Biochar Amendment Improved Growth and Yield of Fragrant Rice and Reduced Arsenic (As) Accumulation under As-contaminated Irrigation Water - Umair Ashraf; Talat Mansha; Shakeel Ahmad Anjum; James DeDecker; Abrar Hussain; Fahd Rasul; Muhmmad Abrar; Muhammad Ishfaq (Water, Air, & Soil Pollution, 2025)

In-cloud ice accretion and performance degradation of UAV propellers in forward flight: An experimental study - Manaf Muhammed; Derek Harvey; Hassan Abbas Khawaja; Muhammad Shakeel Virk; Gelareh Momen (Cold Regions Science and Technology, 2025)

Modeling the impact of climate warming on tomato phenology - Shakeel Ahmad; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Muhammad Ali Khan; Mukhtar Ahmed; Carol Jo Wilkerson; Gerrit Hoogenboom (Agricultural and Forest Meteorology, 2025)

DFT, GC-MS analysis and biological evaluation of Limbarda crithmoides L. Dumort essential oil; an important edible halophyte grown in Pakistan - Muhammad Iltaf; Shah Iram Niaz; Muhammad Kashif Majeed; Muhammad Saleem; Mubarak Shah; Muhammad Ali; Syed Shakeel Abbas; Adnan Amin (Natural Product Research, 2025)

Advancing climate modeling: a multi-framework methodology for evaluating GCMs and predicting drought trends - Muhammad Shakeel; Hussnain Abbas; Zulfiqar Ali; Maysaa Elmahi Abd Elwahab; Ehtesham Asharf; Amna Nazeer (Acta Geophysica, 2025)

An XAI-driven diagnostic framework to investigate the predictive power of building features to enhance EPC ratings in detached houses - Hafiz Muhammad Shakeel; Shamaila Iram; Richard Hill; Hafiz Muhammad Athar Farid; Philip Brown; Hassam Ur Rehman (Energy and Buildings, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Urban walkability assessment: methods and implications for city planning - Hamza Chaudhary; Shakeel Mahmood; Yuping Su; Muhammad Sajid Mehmood; Muhammad Irfan Ahamad (Environment, Development and Sustainability, 2025)

A novel Bi-weight Mid Correlation Coefficient Divergence (BMCCD) approach for multi-model ensemble-based drought assessment - Mahrukh Yousaf; Laraib Shafique; Sadia Qamar; Muhammad Shakeel; Farman Ali; Zulfiqar Ali (Environmental Monitoring and Assessment, 2025)

A novel framework for future drought characterization under ranked-based subset selection and weighted aggregative multi-modal ensemble of global climate models - Muhammad Shakeel; Hussnain Abbas; Zulfiqar Ali; Aqil Tariq; Mansour Almazroui; Shuraik Kader (Journal of Environmental Management, 2025)

Foliar Application of Silicon Alleviates Drought Stress in Chickpea (Cicer arietinum L.) by Improving Growth, Photosynthetic and Antioxidant Metabolism - Muhammad Faizan Ali; Mukhtar Ahmed; Laiba Mukhtar; Nadir Ali; Ghulam Qadir; Rifat Hayat; Shakeel Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Development of a Novel Multi-Model Ensemble Weighting Scheme for Improved Drought Assessment - Mahrukh Yousaf; Ali Iqbal; Sadia Qamar; Muhammad Shakeel; Maryam Ilyas; Zulfiqar Ali; Rizwan Niaz (Water Conservation Science and Engineering, 2025)

Assessing Human-Wildlife Conflict in Lakki Marwat, Pakistan: Economic Impacts and People’s Perceptions - Tanveer Khan; Shakeel Ahmad; Tahir Mehmood; Sajjad Rais Khan; Daulat Ullah Khan; Salman Khan; Muhammad Ullah; Ejaz Rahim (European Journal of Wildlife Research, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Salicylic acid-induced defense responses against a newly identified cotton pathogen, Pantoea vagans - Muneeb Anwer; Muhammad Waqas Azam; Muhammad Taimoor Shakeel; Anam Moosa; Hongwei Zhao; Muhammad Aslam Farooqi; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi; Huda Alghamdi; Ambreen Maqsood; Muhammad Naveed Aslam (Physiological and Molecular Plant Pathology, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Spectrum of BRCA1/2 pathogenic variants in Southern and Western Asia-a systematic review - Samra Khan; Ikram A. Burney; Mahrukh Nasir; Humaira Saleem; Muhammad Irfan; Muhammad Shakeel; Ishtiaq Ahmad Khan (Mutation Research - Reviews in Mutation Research, 2025)

Distribution modelling and future prediction of a threatened species - Heracleum candicans Wall. ex DC.; Within the framework of biotic and abiotic interactions - Jawad Hussain; Shujaul Mulk Khan; Muhammad Shakeel Khan; Zafeer Saqib; Abdullah; Zeeshan Ahmad; Maria Shah; Nazir Mohammad; Zareena Batool; Amir Sohail; Jie Liu (Journal of Environmental Management, 2025)

A new statistical framework for future drought assessment – mutual information-based regional integrated standardized multicriteria decision for drought assessment - Muhammad Shakeel; Zulfiqar Ali (Theoretical and Applied Climatology, 2025)

Assessment of Climate Change Impact on Potato-Potato Cropping System Under Semi-arid Environment and Designing of Adaptation Strategies - Sahrish Naz; Mukhtar Ahmed; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Abdul Ghani; Muhammad Ali; Tahir Hussain Awan; Noreen Samad; Muhammad Aasim; Sezai Ercisli; et al. (Potato Research, 2025)

First Insights on Sowing Time and Cultivar Selection of Sweet Corn for Optimal Yield and Shelf Life Under Agro-Climatic Conditions of Multan - Iqra Zakir; Shakeel Ahmad; Muhammad Shahzad Saleem; Sajjad Hussain; Halima Nawaz; Talaat Ahmed; Muhammad Fasih Khalid (International Journal of Plant Production, 2025)

Exploitation of genetic variation to enhance grain nutrient contents in bread wheat through conventional and molecular approaches - Rabia Ikram; Sania Begum; Nasr Ullah Khan; Muhammad Mohibullah; Muhammad Shakeel; Salma Shaheen; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Iram Ijaz; Muhammad Yasin (Cereal Research Communications, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Adaptive ensemble weighting for GCMs to enhance future drought characterization under various climate change scenarios - Muhammad Shakeel; Hussnain Abbas; Ayesha Waseem; Zulfiqar Ali (Theoretical and Applied Climatology, 2025)

Quantifying LID impact: A modified metric for enhanced flood mitigation and urban resilience - Shakeel Ahmad; Haifeng Jia; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr (Resources, Conservation and Recycling, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

Enhancing drought projection reliability: a framework for optimal GCM selection, aggregation, and trend analysis under shared socioeconomic pathways - Muhammad Shakeel; Hussnain Abbas; Zulfiqar Ali; Muhammad Mohsin (Theoretical and Applied Climatology, 2025)

Flood characteristics and risk analysis in small watersheds on the Loess Plateau under extreme heavy rainfall - Muhammad Imran; Jingming Hou; Tian Wang; Qingshi Zhou; Donglai Li; Majid Habib Khan; Irfan Ullah; Rana Shahzad Noor; Muhammad Umair; Shakeel Hussain (Natural Hazards, 2025)

First report of leaf spot of Wodyetia bifurcata caused by Alternaria alternata in Pakistan - Muhammad Abu Bakar; Roshaan Ahmed; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel (Physiological and Molecular Plant Pathology, 2025)

Qualitative Traits of Heat Stressed Bread Wheat (Triticum aestivum L.) were Improved by Exogenous Potassium Signaling - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Abdul Shakoor; Khalid Mahmood; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2025)

Building resilient urban drainage systems by integrated flood risk index for evidence-based planning - Shakeel Ahmad; Xuanrong Peng; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr; Haifeng Jia (Journal of Environmental Management, 2025)

A Global Perspective on the Biology, Impacts and Management Options of Leptochloa chinensis, a Noxious Weed of Direct-seeded Rice—A Review - Muhammad Ishfaq; Zarina Batool; Usman Zulfiqar; Muhammad Ahmad; Fasih Ullah Haider; Nasim Ahmed; Saddam Hussain; Shakeel Ahmed Anjum; Nadeem Akbar (Journal of Crop Health, 2025)

Optimization-based innovative approach for economical design of reinforced concrete isolated footings - Junaid Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mansoor Shakeel (Innovative Infrastructure Solutions, 2025)

Retraction Note: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity andAmeliorative Effects of Cinnamomum cassia in Sprague–Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

Probiotic potential and biotechnological characterization of the selected enterococcal strains - Abrar Hussain; Muhammad Shakeel; Muhammad Tanweer Khan; Syed Abid Ali (Food Bioscience, 2025)

Exploring heat transfer in freezing supercooled water droplet through high-speed infrared thermography - Hassan Abbas Khawaja; Samaneh Keshavarzi; Adeel Yousuf; Manaf Muhammed; Muhammad Shakeel Virk; Derek Harvey; Gelareh Momen (Cold Regions Science and Technology, 2025)

Real-time remote corn growth monitoring system using plant wearable fiber Bragg grating sensor - Wei Zhang; Muhammad Awais; Syed Muhammad Zaigham Abbas Naqvi; Yani Xiong; Linze Li; Yiheng Zang; Shakeel Ahmed; Junfeng Wu; Hao Zhang; Mukhtar Iderawumi Abdulraheem; Vijaya Raghavan; Jianfeng Ping; et al. (Computers and Electronics in Agriculture, 2024)

Remediation of chromium contaminated water and soil by nitrogen and iron doped biochars - Shakeel Ahmad; Xiaomei Liu; Linan Liu; Muhammad Waqas; Junhui Zhang; Muhammad Azher Hassan; Shicheng Zhang; Bo Pan; Jingchun Tang (Science of The Total Environment, 2024)

Spatial distribution, ecological and human health risks of potentially toxic elements (PTEs) in river Ravi, Pakistan: A comprehensive study - Muhammad Irfan Ahamad; Adnanul Rehman; Muhammad Sajid Mehmood; Shakeel Mahmood; Zeeshan Zafar; Heli Lu; Wanfu Feng; Siqi Lu (Environmental Research, 2024)

RETRACTED ARTICLE: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Retraction Note: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2024)

Spatial modeling of soil erosion potential in the Panjkora Basin, Eastern Hindu Kush: integrated RUSLE and geospatial approaches - Shakeel Mahmood; Nayab Naeem; Muhammad Irfan Ahamad; Zara Tariq; Jinxi Song (Environment, Development and Sustainability, 2024)

Knockdown of the glucosamine-6-phosphate N-acetyltransferase gene by RNA interference enhances the virulence of entomopathogenic fungi against rice leaffolder Cnaphalocrocis medinalis - Muhammad Shakeel; Ashraf Khan; Juan Du; Abdul Basit; Guangming Yang; Khalid Haddi; Sohail Abbas; Aleena Alam; Shangwei Li (Pesticide Biochemistry and Physiology, 2024)

Carbon based nanocomposites, surface functionalization as a promising material for VOCs (volatile organic compounds) treatment - Farooq Nawaz; Muhammad Ali; Shakeel Ahmad; Yang Yong; Suhaib Rahman; Muhammad Naseem; Sadam Hussain; Abdul Razzaq; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Chemosphere, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Changes in characteristics of spermatogonial stem cells in response to heat stress in stallions - Muhammad Shakeel; Minjung Yoon (Theriogenology, 2024)

Improving future drought predictions – a novel multi-method framework based on mutual information for subset selection and spatial aggregation of global climate models of precipitation - Muhammad Shakeel; Zulfiqar Ali (Stochastic Environmental Research and Risk Assessment, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Deep Dynamic Weights for Underwater Image Restoration - Hafiz Shakeel Ahmad Awan; Muhammad Tariq Mahmood (Journal of Marine Science and Engineering, 2024)
Underwater imaging presents unique challenges, notably color distortions and reduced contrast due to light attenuation and scattering. Most underwater image enhancement methods first use linear transformations for color compensation and then enhance the image. We observed that linear transformation for color compensation is not suitable for certain images. For such images, non-linear mapping is a better choice. This paper introduces a unique underwater image restoration approach leveraging a streamlined convolutional neural network (CNN) for dynamic weight learning for linear and non-linear mapping. In the first phase, a classifier is applied that classifies the input images as Type I or Type II. In the second phase, we use the Deep Line Model (DLM) for Type-I images and the Deep Curve Model (DCM) for Type-II images. For mapping an input image to an output image, the DLM creatively combines color compensation and contrast adjustment in a single step and uses deep lines for transformation, whereas the DCM employs higher-order curves. Both models utilize lightweight neural networks that learn per-pixel dynamic weights based on the input image’s characteristics. Comprehensive evaluations on benchmark datasets using metrics like peak signal-to-noise ratio (PSNR) and root mean square error (RMSE) affirm our method’s effectiveness in accurately restoring underwater images, outperforming existing techniques.

Endophytic Bacillus spp. Mediated Plant Growth Promotion of Tomato Seedlings and Suppression of Meloidogyne incognita and Fusarium oxysporum Disease Complex - Ambreen Maqsood; Muhammad Naveed Aslam; Huma Khaliq; Muhammad Taimoor Shakeel; Haiyan Wu; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Spatial variation in iodine content with relation to soil physicochemical properties in lower Himalayan region - Jawad Ali; Muhammad Mohiuddin; Xinfeng Wang; Zahid Hussain; Muhammad Irshad; Munir Zia; Rashid Pervez; Mohammad K. Okla; Shakeel Ahmad (Environmental Research, 2024)

Sustainable production of bread wheat under terminal heat stress: an investigation of foliar selenium-mediated biochemical regulations in association with yield - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Muhammad Aown Sammar Raza; Shakeel Ahmad Anjum; Arshad Hussain (Cereal Research Communications, 2024)

Application of Synthetic Iron Oxyhydroxide with Influencing Factors for Removal of As(V) and As(III) from Groundwater - Shakeel Ahmed Talpur; Muhammad Yousuf Jat Baloch; Chunli Su; Javed Iqbal; Aziz Ahmed; Hafeez Ahmed Talpur (Journal of Earth Science, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Rockfall susceptibility assessment along M-2 Motorway in Salt Range, Pakistan - Shakeel Mahmood; Farman Atique; Adnanul Rehman; Shaker Mahmood Mayo; Muhammad Irfan Ahamad (Journal of Applied Geophysics, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Insight into microplastics in the aquatic ecosystem: Properties, sources, threats and mitigation strategies - Nisar Ali; Muhammad Hamid Khan; Muhammad Ali; Sidra; Shakeel Ahmad; Adnan Khan; Ghulam Nabi; Farman Ali; Mohamed Bououdina; George Z. Kyzas (Science of The Total Environment, 2024)

Foot and mouth disease (FMD) epidemiology in small ruminants by identifying antibodies for non-structural and structural proteins with a sequential screening approach: A cross-sectional study - Muhammad Shakeel Khaliq; Mobeen Sarwar; Farhat Nazir Awan; Halima Sadia; Aamir Saleem; Syed Abdul Khaliq; Muhammad Hassan Mushtaq; Mamoona Chaudhry; Abdul Rehman (Small Ruminant Research, 2024)

Integration of Exponential Weighted Moving Average Chart in Ensemble of Precipitation of Multiple Global Climate Models (GCMs) - Muhammad Shakeel; Zulfiqar Ali (Water Resources Management, 2024)

Integrated Use of Manure and Urea Fertilizer Economically Improve Wheat Production and Nitrogen Indices in a Range of Tillage Practices - Ihsan Muhammad; Jun Wang; Upendra M. Sainju; Ahmad Khan; Li Yang; Shakeel Ahmand; Yining Zhang; Shah Fahad; Xun Bo Zhou; Weijun Shen (Journal of Plant Growth Regulation, 2024)

Geo-spatial assessment of pluvial floods in city district Lahore, Pakistan - Muhammad Ali; Shakeel Mahmood (Environmental Monitoring and Assessment, 2024)

A practical tool for structural design optimization of steel frames: development and application for parametric analysis - Umair Ali; Rizwan Azam; Mansoor Shakeel; Muhammad Adil; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2024)

Development of a new hybrid ensemble method for accurate characterization of future drought using multiple global climate models - Mahrukh Yousaf; Zulfiqar Ali; Muhammad Mohsin; Maryam Ilyas; Muhammad Shakeel (Stochastic Environmental Research and Risk Assessment, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Transcriptomic analysis of Ralstonia solanacearum in response to antibacterial volatiles of Bacillus velezensis FZB42 - Hafiz Abdul Samad Tahir; Qurban Ali; Faheem Uddin Rajer; Qaisar Shakeel; Waqqas Gillani; Rana Binyamin; Hafiz Muhammad Abdullah Tayyab; Abdur Rashid Khan; Qin Gu; Xuewen Gao; Huijun Wu (Archives of Microbiology, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

A generalized procedure for joint monitoring and probabilistic quantification of extreme climate events at regional level - Aamina Batool; Zulfiqar Ali; Muhammad Mohsin; Muhammad Shakeel (Environmental Monitoring and Assessment, 2023)

Sustainable production of bread wheat using laser land levelling and sowing methods as potent regulators of carbon sequestration, fuel consumption and water use in the arid environment of Bahawalpur, Pakistan - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Shakeel Ahmad Anjum; Arshad Hussain (Irrigation and Drainage, 2023)
Excessive use of water in wheat is associated with high fuel consumption and the emission of carbon dioxide into the environment. This study was conducted with the objectives to decrease water use and the associated fuel consumption and carbon dioxide emissions and to improve the productivity of wheat on a sustainable basis using LASER levelling and sowing methods as potent modulators of these adversities. The experiment was conducted in the research area of the Agronomic Research Station Bahawalpur over 3 years using a split‐plot experimental design and four replications. Treatments contained LASER levelling in the main plot (L 0 = no LASER levelling, L 1 = LASER levelling) and sowing methods in split plots (S 1 = broadcast, S 2 = ridge sowing and S 3 = drill sowing). Less water use, fuel consumption and emission of carbon dioxide were quantified under ‘LASER levelling’ and under ‘ridge sowing’ compared to other treatments. Regarding wheat crop productivity, the same treatment combination (LASER levelling and ridge sowing) resulted in more fertile tillers, grains per spike, 1000‐grain weight and grain yield. Therefore, we concluded that ‘LASER levelling’ and ‘ridge sowing’ have the potential to reduce the cost involved and environmental pollution (by reducing fuel consumption) and improve water use efficiency, grain yield and yield components of wheat compared to other treatments. Moreover, strong negative associations of water use, fuel consumption and carbon dioxide emissions with the grain yield of wheat were recorded.

Translating environmental corporate social responsibility into environmental performance and competitive advantage: a moderated mediation model - Ahmad Qammar; Rabiya Sagheer; Muhammad Shakeel Aslam (Environmental Science and Pollution Research, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Does Exogenous Selenium Elicited Biochemical Regulations Make Economic Improvements in Terminally Heat-Stressed Bread Wheat? An Evidence from Marginal Analysis - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Bao-Luo Ma; Shakeel Ahmad Anjum; Arshad Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Effects of insulin-like growth factor-1 on the proliferation and apoptosis of stallion testicular cells under normal and heat stress culture conditions - Muhammad Shakeel; Minjung Yoon (Animal Reproduction Science, 2023)

Spatio-temporal analysis of river channel pattern in lower course of River Ravi using GIS and remote sensing - Noor-ul Huda; Shakeel Mahmood; Rida Sajjid; Muhammad Irfan Ahamad (Applied Geomatics, 2023)

Use of remote sensing-based pressure-state-response framework for the spatial ecosystem health assessment in Langfang, China - Anam Ashraf; Muhammad Athar Haroon; Shakeel Ahmad; Ahmed Samir Abowarda; Chunyue Wei; Xuehua Liu (Environmental Science and Pollution Research, 2023)

Estimation of phytoextraction potential of selected halophytes for accumulation of heavy metals from wetland saline soil - Muhammad Waris; Jameel Ahmed Baig; Farah Naz Talpur; Tasneem Gul Kazi; Hassan Imran Afridi; Sadia Shakeel (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Arsenic Removal from Groundwater Using Iron Pyrite: Influence Factors and Removal Mechanism - Muhammad Yousuf Jat Baloch; Chunli Su; Shakeel Ahmed Talpur; Javed Iqbal; Kulvinder Bajwa (Journal of Earth Science, 2023)

Mixed inoculation of dark septate endophytic and ericoid mycorrhizal fungi in different proportions improves the growth and nutrient content of blueberry seedlings - Xiaolan Guo; Yaqin Wang; Jinbin Hu; Delu Wang; Jianbing Wang; Muhammad Shakeel (Plant Biosystems, 2023)

First report of leaf spot of Aloe vera caused by Curvularia spicifera in Pakistan - Roshaan Ahmed; Muhammad Naveed Aslam; Anam Moosa; Muhammad Taimoor Shakeel; Ambreen Maqsood (Journal of Plant Pathology, 2023)

A comparative study based on performance and techno-economic analysis of different strategies for PV-Electrolyzer (green) hydrogen fueling incinerator system - Osama Majeed Butt; Muhammad Shakeel Ahmad; Teong Kai Lun; Hang Seng Che; H. Fayaz; Nasrudin Abd Rahim; Krzysztof K.K. Koziol; Neyara Radwan; Mohammad Amir Khan; Nadeem A Khan; Lakhveer Singh (Waste Management, 2023)

Physiological and transcriptomic study reveal SeNPs-mediated AsIII stress detoxification mechanisms involved modulation of antioxidants, metal transporters, and transcription factors in Glycine max L. (Merr.) roots - Muhammad Zeeshan; Yu Xin Hu; Xiao Hong Guo; Chen Yu Sun; Abdul Salam; Shakeel Ahmad; Ihsan Muhammad; Jamal Nasar; Mohammad Shah Jahan; Shah Fahad; Xun Bo Zhou (Environmental Pollution, 2023)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

Genome wide and evolutionary analysis of heat shock protein 70 proteins in tomato and their role in response to heat and drought stress - Muhammad Zulfiqar Ahmad; Zamarud Shah; Arif Ullah; Shakeel Ahmed; Bushra Ahmad; Afrasyab Khan (Molecular Biology Reports, 2022)

Low Irrigation Water Improves Biomass Saccharification, Photosynthetic Pigments of Maize, and Minimizes Nitrate Nitrogen Leaching - Ihsan Muhammad; Li Yang; Shakeel Ahmad; Saqib Farooq; Ahmad Khan; Muhammad Zeeshan; Xun Bo Zhou (Journal of Soil Science and Plant Nutrition, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

First report of cucumber-infecting cucurbit chlorotic yellows virus (CCYV) associated with cucurbit yellows disease in Pakistan - Muhammad Nouman; Tahir Farooq; Rashida Parveen; Ummad ud-Din Umar; Muhammad Naveed Aslam; Mahmoud Moustafa; Muhammad Taimoor Shakeel (Journal of Plant Pathology, 2022)

First report of post-harvest brown spot of lemon caused by Alternaria alternata in Pakistan - Anam Moosa; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Tanvir Ahmad; Mahmoud Moustafa; Mohammed Al-Shehri; Ahmed Al-Emam (Journal of Plant Pathology, 2022)

Impact of Climate Change on Dryland Agricultural Systems: A Review of Current Status, Potentials, and Further Work Need - Mukhtar Ahmed; Rifat Hayat; Munir Ahmad; Mahmood ul-Hassan; Ahmed M. S. Kheir; Fayyaz ul-Hassan; Muhammad Habib ur-Rehman; Farid Asif Shaheen; Muhammad Ali Raza; Shakeel Ahmad (International Journal of Plant Production, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Enhanced photocatalytic potential of TiO2 nanoparticles in coupled CdTiO2 and ZnCdTiO2 nanocomposites - Shakeel Khan; Muhammad Sadiq; Niaz Muhammad (Environmental Science and Pollution Research, 2022)

Natural plant extracts mediated expression regulation of TGF-β receptors and SMAD genes in human cancer cell lines - Ammara Jabeen; Qaisar Mansoor; Tayyaba Zainab; Ammad Ahmad Farooqi; Mazhar Qayyum; Aqsa Mansha; Arifa Shakeel; Muhammad Sheeraz Ahmad (Molecular Biology Reports, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Volkamer Lemon Tetraploid Rootstock Transmits the Salt Tolerance When Grafted with Diploid Kinnow Mandarin by Strong Antioxidant Defense Mechanism and Efficient Osmotic Adjustment - Muhammad Fasih Khalid; Raphael Morillon; Muhammad Akbar Anjum; Shaghef Ejaz; Muhammad Junaid Rao; Shakeel Ahmad; Sajjad Hussain (Journal of Plant Growth Regulation, 2022)

Identification of putative genetic variants in major depressive disorder patients in Pakistan - Sarah Rizwan Qazi; Muhammad Irfan; Zoobia Ramzan; Muhammad Jahanzaib; Maleeha Zaman Khan; Mahrukh Nasir; Muhammad Shakeel; Ishtiaq Ahmad Khan (Molecular Biology Reports, 2022)

A spreadsheet-based tool for optimal design of reinforced concrete cantilever retaining walls - Mansoor Shakeel; Rizwan Azam; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2022)

Economic assessment of water-saving irrigation management techniques and continuous flooded irrigation in different rice production systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Fahimuddin Shah; Shakeel Ahmad Anjum; Muhammad Farooq (Paddy and Water Environment, 2022)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Impact of the mixture verses solo residue management and climatic conditions on soil microbial biomass carbon to nitrogen ratio: a systematic review - Ihsan Muhammad; Jun Wang; Ahmad Khan; Shakeel Ahmad; Li Yang; Izhar Ali; Muhammad Zeeshan; Saif Ullah; Shah Fahad; Shamsher Ali; Xun Bo Zhou (Environmental Science and Pollution Research, 2021)

Distinct genetic landscape and a low response to doxorubicin in a luminal-A breast cancer cell line of Pakistani origin - Muhammad Shakeel; Salman Ahmed Khan; Anum Jabeen Mughal; Muhammad Irfan; Daniel C. Hoessli; M. Iqbal Choudhary; Muhammad Aurongzeb; Ishtiaq Ahmad Khan (Molecular Biology Reports, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Assessing the impact of climatic change on discharge in Swat river basin using fuzzy logic model - Muhammad Dawood; Atta-ur Rahman; Shakeel Mahmood; Ghani Rahman; Shah Nazir (Arabian Journal of Geosciences, 2021)

Compact maize canopy improves radiation use efficiency and grain yield of maize/soybean relay intercropping system - Muhammad Ali Raza; Liang Cui; Imran Khan; Atta Mohi Ud Din; Guopeng Chen; Muhammad Ansar; Mukhtar Ahmed; Shakeel Ahmad; Abdul Manaf; John Kwame Titriku; Ghulam Abbas Shah; Feng Yang; et al. (Environmental Science and Pollution Research, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Phenolic, flavonoid content and radical scavenging activity of Smilax china with its inhibitory potential against clinically important enzymes - Hafiz Ibtesam Ahmad; Haji Muhammad Shoaib Khan; Naveed Akhtar; Shakeel Ijaz (Natural Product Research, 2021)

A Core Logging, Machine Learning and Geostatistical Modeling Interactive Approach for Subsurface Imaging of Lenticular Geobodies in a Clastic Depositional System, SE Pakistan - Umar Ashraf; Hucai Zhang; Aqsa Anees; Hassan Nasir Mangi; Muhammad Ali; Xiaonan Zhang; Muhammad Imraz; Saiq Shakeel Abbasi; Ayesha Abbas; Zaheen Ullah; Jar Ullah; Shucheng Tan (Natural Resources Research, 2021)

Exogenous Application of Melatonin Induces Tolerance to Salt Stress by Improving the Photosynthetic Efficiency and Antioxidant Defense System of Maize Seedling - Shakeel Ahmad; Wenwen Cui; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Wennan Su; Tehseen Javed; Hamed A. El-Serehy; Zhikuan Jia; Qingfang Han (Journal of Plant Growth Regulation, 2021)

An integrated approach to evaluate the unconventional hydrocarbon generation potential of the Lower Goru Formation (Cretaceous) in Southern Lower Indus basin, Pakistan - Muhsan Ehsan; Hanming Gu; Abid Ali; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Muhammad Armaghan Faisal Miraj; Munawar Shah (Journal of Earth System Science, 2021)

Sowing Dates and Cultivars Mediated Changes in Phenology and Yield Traits of Cotton-Sunflower Cropping System in the Arid Environment - Muhammad Tariq; Zartash Fatima; Pakeeza Iqbal; Kamrun Nahar; Shakeel Ahmad; Mirza Hasanuzzaman (International Journal of Plant Production, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Assessment of environmental impact on essential and toxic elements composition in natural honeys by using inductively coupled plasma mass spectrometry - Atia Gohar; Muhammad Shakeel (Environmental Science and Pollution Research, 2021)

Quantification of Climate Warming and Crop Management Impacts on Phenology of Pulses-Based Cropping Systems - Zartash Fatima; Atique-ur-Rehman; Ghulam Abbas; Pakeeza Iqbal; Iqra Zakir; Muhammad Azam Khan; Ghulam Mujtaba Kamal; Mukhtar Ahmed; Shakeel Ahmad (International Journal of Plant Production, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Hormonal changes with uniconazole trigger canopy apparent photosynthesis and grain filling in wheat crop in a semi-arid climate - Irshad Ahmad; Muhammad Kamran; Xiangping Meng; Shahzad Ali; Shakeel Ahmad; Zhiqiang Gao; Tiening Liu; Qingfang Han (Protoplasma, 2021)

Economic output, export, fossil fuels, non-fossil fuels and energy conservation: evidence from structural break models with VECMs in South Asia - Muhammad Shakeel (Environmental Science and Pollution Research, 2021)

Sowing Date and Hybrid Choice Matters Production of Maize–Maize System - Ghulam Abbas; Shakeel Ahmad; Mubshar Hussain; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Farooq (International Journal of Plant Production, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Genome-wide analysis of glutathione S-transferase gene family in G. max - Muhammad Zulfiqar Ahmad; Jamal Abdul Nasir; Shakeel Ahmed; Bushra Ahmad; Aiman Sana; Said Salman; Zamarud Shah; CunYi Yang (Biologia, 2020)

Energy-GDP-exports nexus and energy conservation: evidence from Pakistan and South Asia - Muhammad Shakeel; Abdul Salam (Environmental Science and Pollution Research, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Foliar application of melatonin delay leaf senescence in maize by improving the antioxidant defense system and enhancing photosynthetic capacity under semi-arid regions - Shakeel Ahmad; Wennan Su; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Tehseen Javed; Qingfang Han (Protoplasma, 2020)

Evaluating the combination of Metarhizium anisopliae and an enhanced form of diatomaceous earth (Grain-Guard) for the environmentally friendly control of stored grain pests - Nadia Saeed; Waqas Wakil; Muhammad Farooq; Muhammad Shakeel; Muhammad Shahid Arain; Qaiser Shakeel (Environmental Monitoring and Assessment, 2020)

Spatio-statistical analysis of rainfall fluctuation, anomaly and trend in the Hindu Kush region using ARIMA approach - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Shakeel Mahmood; Ghani Rahman; Kamran Azam (Natural Hazards, 2020)

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Amna Saleem; Amir Shakeel; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Application of Uniconazole Improves Photosynthetic Efficiency of Maize by Enhancing the Antioxidant Defense Mechanism and Delaying Leaf Senescence in Semiarid Regions - Irshad Ahmad; Muhammad Kamran; Wennan Su; Wang Haiqi; Shahzad Ali; Bayasgalan Bilegjargal; Shakeel Ahmad; Tiening Liu; Tie Cai; Qingfang Han (Journal of Plant Growth Regulation, 2019)

A genome-wide approach to the comprehensive analysis of GASA gene family in Glycine max - Muhammad Zulfiqar Ahmad; Aiman Sana; Arshad Jamil; Jamal Abdul Nasir; Shakeel Ahmed; Muhammad Uzair Hameed; Abdullah (Plant Molecular Biology, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Ameliorative Effects of Selenium in ZnO NP-Induced Oxidative Stress and Hematological Alterations in Catla catla - Muhammad Saleem Asghar; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Khan; Muhammad Shakeel; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2018)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Assessing the impact of climate variability on maize using simulation modeling under semi-arid environment of Punjab, Pakistan - Ishfaq Ahmed; Muhammad Habib ur Rahman; Shakeel Ahmed; Jamshad Hussain; Asmat Ullah; Jasmeet Judge (Environmental Science and Pollution Research, 2018)

Drought tolerance in citrus rootstocks is associated with better antioxidant defense mechanism - Sajjad Hussain; Muhammad Fasih Khalid; Muhammad Saqib; Shakeel Ahmad; Waseem Zafar; Muhammad Junaid Rao; Raphaël Morillon; Muhammad Akbar Anjum (Acta Physiologiae Plantarum, 2018)

Effectiveness of an improved form of insecticide-based diatomaceous earth against four stored grain pests on different grain commodities - Nadia Saeed; Muhammad Farooq; Muhammad Shakeel; Misbah Ashraf (Environmental Science and Pollution Research, 2018)

Identification of Hydrocarbon Potential of Talhar Shale: Member of Lower Goru Formation Using Well Logs Derived Parameters, Southern Lower Indus Basin, Pakistan - Muhsan Ehsan; Hanming Gu; Malik Muhammad Akhtar; Saiq Shakeel Abbasi; Zaheen Ullah (Journal of Earth Science, 2018)

Impact of city effluents on water quality of Indus River: assessment of temporal and spatial variations in the southern region of Khyber Pakhtunkhwa, Pakistan - Ilham Khan; Azim Khan; Muhammad Sohail Khan; Shabnam Zafar; Asma Hameed; Shakeel Badshah; Shafiq Ur Rehman; Hidayat Ullah; Ghazala Yasmeen (Environmental Monitoring and Assessment, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Earliness index deters Pectinophora gossypiella incidence on advanced cultivars of Bt cotton - Muhammad Rafiq Shahid; Muhammad Shakeel; Muhammad Farooq; Muhammad Shahid Arain; Chaudhary Muhammad Shahid Hanif; Haichen Yin; Muhammad Akram; Saghir Ahmad (Arthropod-Plant Interactions, 2018)

RETRACTED ARTICLE: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

RETRACTED ARTICLE: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity and Ameliorative Effects of Cinnamomum cassia in Sprague-Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

Gene expression studies of reference genes for quantitative real-time PCR: an overview in insects - Muhammad Shakeel; Alicia Rodriguez; Urfa Bin Tahir; Fengliang Jin (Biotechnology Letters, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests - Misbah Ashraf; Muhammad Farooq; Muhammad Shakeel; Naima Din; Shahbaz Hussain; Nadia Saeed; Qaiser Shakeel; Nasir Ahmed Rajput (Environmental Science and Pollution Research, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Impact of Dysdercus koenigii Fabricius (Hemiptera: Pyrrhcoridae) density-dependent population on agronomic and qualitative characteristics of different transgenic cotton varieties - Muhammad Rafiq Shahid; Muhammad Farooq; Muhammad Shakeel; Abid Mahmood; Muhammad Dildar Gogi (Phytoparasitica, 2017)

Eco-Friendly Synthesis of Silver Nanoparticles Through Economical Methods and Assessment of Toxicity Through Oxidative Stress Analysis in the Labeo Rohita - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Asghar; Muhammad Shakeel; Muhammad Fakhar -e -Alam (Biological Trace Element Research, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

Carnivores’ diversity and conflicts with humans in Musk Deer National Park, Azad Jammu and Kashmir, Pakistan - Shakeel Ahmad; Shoaib Hameed; Hussain Ali; Tauheed Ullah Khan; Tahir Mehmood; Muhammad Ali Nawaz (European Journal of Wildlife Research, 2016)

RETRACTED ARTICLE: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2016)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

Toxicity of Nano-Titanium Dioxide (TiO2-NP) Through Various Routes of Exposure: a Review - Muhammad Shakeel; Farhat Jabeen; Samina Shabbir; Muhammad Saleem Asghar; Muhammad Saleem Khan; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Alleviation of chromium toxicity by glycinebetaine is related to elevated antioxidant enzymes and suppressed chromium uptake and oxidative stress in wheat (Triticum aestivum L.) - Shafaqat Ali; Aaifa Chaudhary; Muhammad Rizwan; Hafiza Tania Anwar; Muhammad Adrees; Mujahid Farid; Muhammad Kashif Irshad; Tahir Hayat; Shakeel Ahmad Anjum (Environmental Science and Pollution Research, 2015)

Molecular Characterization of Chenopodium album Chloroplast Small Heat Shock Protein and Its Expression in Response to Different Abiotic Stresses - Noor Ul Haq; Muhammad Ammar; Asghari Bano; Dawn S. Luthe; Scott A. Heckathorn; Samina N. Shakeel (Plant Molecular Biology Reporter, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Evaluation of synthetic hexaploid wheats (derivative of durum wheats and Aegilops tauschii accessions) for studying genetic diversity using randomly amplified polymorphic DNA (RAPD) markers - Muhammad Shakeel; Muhammad Ilyas; Mujeeb Kazi (Molecular Biology Reports, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and nitrogen management of fine transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Cecilia Manuela Tojo Soler; Hakoomat Ali; Muhammad Zia-Ul-Haq; Jakarat Anothai; Abid Hussain; Gerrit Hoogenboom; Mirza Hasanuzzaman (Precision Agriculture, 2012)

Photostability and Interaction of Ascorbic Acid in Cream Formulations - Iqbal Ahmad; Muhammad Ali Sheraz; Sofia Ahmed; Riaz Hussain Shaikh; Faiyaz H. M. Vaid; Saif ur Rehman Khattak; Shakeel A. Ansari (AAPS PharmSciTech, 2011)